Prevalence of Pre Diabetes and Type 2 Diabetes Mellitus among cement industry workers - Meo, Sultan Ayoub (Pak J Med Sci, 2020)
OBJECTIVES: Occupational and environmental pollution have become an imperative jeopardy for developing devastating metabolic diseases. Limited animal model studies have examined the impact of exposure to cement dust on metabolic conditions. This study aimed to assess the prevalence of pre-diabetes and Type-2 diabetic mellitus (T2DM) among non-smoking cement mill workers. METHODS: This epidemiological cross sectional study was conducted in the “Department of Physiology, College of Medicine, King Saud University, Riyadh, Saudi Arabia” during the period Oct 2016 to June 2017. Initially 310 cement mill workers were interviewed; after the interview and clinical history taking, 186 non-smoking cement mill employees were finally recruited. The cement mill employees were exposed to cement dust-related pollution in a cement industry for eight hours a day for six days a week. The mean age was 36.56 ± 0.78 years, mean BMI was 25.70 ± 0.29 m/kg2, and mean period of employment in the cement industry was 82.77 ± 6.95 months. HbA1c was measured using the Dimension Xpand Plus Integrated Chemistry System (USA). RESULTS: The cement mill employees were divided into three groups: non-diabetics group, with glycated hemoglobin (HbA1c) <5.7%; pre-diabetics group, with HbA1c 5.7-6.4%; and diabetics group, with HbA1c >6.4%. Among the cement mill personnel, 79 (42.47%) were non-diabetics, 28 (15.05%) were pre-diabetics, and 79 (42.47%) were diabetics. The prevalence of pre-diabetes and T2DM among cement mill employees was considerably associated with the period of employment in the cement industry (p=0.032). CONCLUSIONS: Exposure to cement dust was associated with an increased prevalence of pre- diabetes and T2DM among cement industry employees.